Environmental Impact of Food Retailing, A comparative LCA of organic and conventional food products - Eriksson, Malin (My University, 2015)
The food chain in Sweden is estimated to contribute to one quarter of the total greenhouse gas emissions. Retailers have an important position, as the actor between the food producers and the consumer, to influence the supply chain. The aim of this thesis was to perform a comparative life cycle assessment to investigate the environmental impact of Swedish retailers handling of food products, and see if conventional and organic products are handled in different ways. The study also assessed the retailers opportunity to affect the environmental impacts in the food chain. This was achieved by studying six different food products; apple, banana, deep frozen cod, egg milk and pork. In order to gather information both quantitative and qualitative methods were used. Retailer data were collected from the Swedish retailer Coop through interviews and literature reviews. The study shows that retailers have a small contribution to a food products environmental impact, regardless of impact category studied. The activity that contribute the most to retailers environmental impact on food products is transportation, meanwhile warehouse, operational electricity and heating together only contribute to between 1-20 percent of the retailers total environmental impact. Organic production generates in general lower greenhouse gas emissions than conventional production, meanwhile conventional production results in a lower acidification potential and eutrophication potential than organic production. In future studies a greater collaboration with retailers is preferable in order to receive internal documents and more retailer specific data, this could result in a better understanding of retailers handling of food products and their possibility to affect the food chain.
Keywords: Hållbar utveckling; Annan geovetenskap och miljövetenskap; Sustainable Development; Other Earth and Related Environmental Sciences